(Q, S, R)-dissipativity for switched non-linear delay systems. (February 2023) - Li, Chensong; Fu, Jun; Pang, Hongbo
Abstract: In this paper, we investigate ( Q, S, R ) -dissipativity for a class of switched non-linear systems with time-varying delay based on a state dependent switching law. Firstly, sufficient conditions for ( Q, S, R ) -dissipativity are developed by using Hurwitz convex combination approach, these conditions are provided in terms of linear matrix inequalities (LMIs). Secondly, passivity as a special form of ( Q, S, R ) -dissipativity is preserved for the feedback interconnected switched systems with time-varying delay by the merging switching signal technique. Finally, an example is provided to illustrate the effectiveness of the main results.